Modeling and implementation of sequencing of tasks to Maximize the Processing in an organization (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The main objective of this work is to conceive a practical approach to improve customer’s satisfaction which is generally considered as the pillar of the development of customer fidelity for the company. It is necessary to have a platform which we master to manage to satisfy the customer by studying its needs, by having the capacity to be close and serving him for the shortest deadlines.The waiting time before being served is systematically badly noted by the customers and can cause their dissatisfactions. For that, it is necessary to find a way to decrease the dissatisfaction of the customer by improving the service.We propose in this work, a simple and practical approach for modeling and implementation of a sequencing of tasks to maximize the processing in an organization. This approach respects the constraints of the organization and eliminates any shape of wasting of time at the level of service. She can be personalized for any company, as long as an organizational structure including the actors is defined, the authorities as well as the skills required for every participant in the organization.The problem is mathematically modeled by an integer linear programming and in series solved numerically by respecting rules of priority at the level of the departments. At the end, practical examples to illustrate the work are given.